PENDIDIKAN HUMANISME (KOMPARASI PEMIKIRAN K.H. AHMAD DAHLAN DAN PAULO FREIRE) - Muhammad Najib Alfaruq (Tajdida: Jurnal Pemikiran dan Gerakan Muhammadiyah, 2014)
This study examines how humanism  education by KH Ahmad Dahlan and Paulo Freire, after the data analyzed, in can be concluded that: (a) The concept of humanism education KH.Ahmad Dahlan and Paulo Fereire have characteristics of each, Ahmad Dahlan tried to incorporate aspects of theology in education, while Paulo Freire inspired by many psychological theories that believes humans have had the potenticy in themselves. (B) Thought humanism education from KHAhmad Dahlan and Paulo Friere have similarities in aspects of educational background, education and implementation as well as educational methods. While the difference between the two lies in the education system and teaching model, the background pattern of thought, the system of education and intellectual heritage.